2020
DOI: 10.3390/agronomy10081095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential Effects of Drought on Summer Maize Yield in the Western Guanzhong Plain, China

Abstract: Drought and uneven distribution of precipitation during stages of crop growth exert a severe reduction on crop yield. It is therefore necessary to evaluate the impact of drought on crop yields. In this study, data from a two-year (2016 and 2017) field experiment were used to calibrate and evaluate the parameters of the Decision Support System for the Agrotechnology Transfer (DSSAT) model. The evaluation model was then employed to analyze the impact of potential drought on the yield of summer maize (Zea mays L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…The model calibration data use the phenological period and aboveground biomass of summer maize with plastic mulching in 2019, and the data for model validation use the LAI and soil water content (0-40 cm) of summer maize with plastic mulching in 2020. This study mainly debugs the parameters of the six summer maize genetic cultivars in the CERES-Maize model (Table 2), and the debugging method uses genetic algorithms (Shen, Chen, et al, 2020). Mean error (ME), coefficient of determination (R 2 ), and relative RMSE (nRMSE) were used to evaluate the relative difference between the simulated and observed values.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The model calibration data use the phenological period and aboveground biomass of summer maize with plastic mulching in 2019, and the data for model validation use the LAI and soil water content (0-40 cm) of summer maize with plastic mulching in 2020. This study mainly debugs the parameters of the six summer maize genetic cultivars in the CERES-Maize model (Table 2), and the debugging method uses genetic algorithms (Shen, Chen, et al, 2020). Mean error (ME), coefficient of determination (R 2 ), and relative RMSE (nRMSE) were used to evaluate the relative difference between the simulated and observed values.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…The decision support system for agricultural technology transfer (DSSAT) is one of most widely used crop models for yield prediction (Anar et al., 2019; Dokoohaki et al., 2015; Shen, Xu, et al., 2020; Yakoub et al., 2017), water management (Haberle & Svoboda, 2014; Ben Nouna et al., 2000; Saïdou et al., 2018), and drought reduction (L. Bai et al., 2004; Chen et al., 2013; Igbadun et al., 2008; Shen, Chen, et al., 2020). Crop environment resource synthesis (CERES), a module of DSSAT model, can simulate crop production parameters including growth period and dry matter allocation for crops such as rice ( Oryza sativa L.), maize, and wheat ( Triticum aestivum L.).…”
Section: Introductionmentioning
confidence: 99%
“…10,20 In this region, the potential yield losses due to drought stress can be as high as 88%. 21 To make up for the shortage of precipitation and alleviate the negative effects of drought stress on maize, local farmers always apply irrigation using a border irrigation method at the jointing stage of summer maize. In fact, drought stress may occur at any stage of summer maize growth.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that water and high temperature stress could close crop stomata, which reduced the assimilation rate, and thereby decreased crop productivity 10,20 . In this region, the potential yield losses due to drought stress can be as high as 88% 21 . To make up for the shortage of precipitation and alleviate the negative effects of drought stress on maize, local farmers always apply irrigation using a border irrigation method at the jointing stage of summer maize.…”
Section: Introductionmentioning
confidence: 99%
“…Maize has been among the most prominent crops in China since the early twentieth century with almost 27% share in China's cereal economy. Shaanxi province is located in the northwest maize agroecological region of China (Meng et al 2006), and more than 50% of its cereal production comes from Guanzhong Plain (Shen et al 2020). Decline in maize yield has been predicted in the region due to climate change-induced higher seasonal temperature .…”
Section: Introductionmentioning
confidence: 99%